Inulin nanoparticles and silymarin counteract chlorpromazine-induced injury in the liver and kidney of rats - Mosaad A. Abdel-Wahhab, Nihad I. Eid, Lamiaa A. Ahmed, Ghada M. Ragab, Aziza A. El-Nekeety, Mohamed M. El-Hakim, Nabila S. Hassan (Journal of Applied Pharmaceutical Science, 2017)
The aim of the current study was to evaluate the protective role of inulin nanoparticles (INPs) prepared by the emulsion method alone or plus silymarin (SIL) against chlorpromazine (CPZ)-induced hepatonephrotoxicity in rats. Eleven groups of female Sprague-Dawley rats were treated orally for 3 weeks as follow: control group, the group treated with CPZ (38.7 mg/kg. b.w in 1 ml saline each 72 h), the groups treated with INPs at low (100 mg/kg b.w) or high (200 mg/ kg b.w) dose, the group treated with SIL (50 mg/kg b.w), the groups treated with SIL plus INPs at the two doses and the groups treated with CPZ plus SIL and INPs at the two tested doses. At the end of the treatment period, blood and tissue samples were collected for different biochemical and histological analyses. The results indicated that CPZ induced significant disturbances in liver and kidney function indices, oxidative stress markers, lipid profile, antioxidant enzyme activity and DNA fragmentation as well as the histological changes in the liver and kidney. SIL alone or plus INPs alone at the low or high dose induce insignificant changes in all the tested parameters or pathological changes in the liver and kidney. SIL and INPs at the two doses could induce a pronounced protection in liver and kidney of CPZ-treated animals due to their antioxidant activity and the role of INPs in the enhancement of SIL solubility. It could be concluded that INPs is a promise drug delivery for SIL and could prevent the liver and kidney injury induced by CPZ.
Keywords: Chlorpromazine, Inulin naopartices, silymarin, liver, kidney, oxidative stress.